2008
DOI: 10.1182/blood-2007-08-109843
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the aryl hydrocarbon receptor promotes allograft-specific tolerance through direct and dendritic cell–mediated effects on regulatory T cells

Abstract: VAF347 is a low-molecular-weight compound, which activates the aryl hydrocarbon receptor (AhR). Herein, we report that oral administration of a water-soluble derivative of VAF347 (VAG539) IntroductionDendritic cells (DCs) induce and regulate adaptive immune responses by presenting antigens in an immunogenic or tolerogenic context. [1][2][3] The capacity of DCs to induce specific effector functions in naive T cells designates them as attractive means to stimulate beneficial and suppress detrimental immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
129
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(135 citation statements)
references
References 46 publications
6
129
0
Order By: Relevance
“…Using similar particles, although loaded with PLP 139-151 , the authors also showed that subcutaneous injection could reduce the incidence of EAE; however, unlike intravenous infusion, protection was not 100% [5,94]. Another strategy that focuses on altering DC phenotype is the administration of NPs that agonize the ligand-activated transcription factor aryl hydrocarbon receptor [7,[95][96][97]. The activation of aryl hydrocarbon receptor on DCs supports their differentiation into tolerogenic APCs, which supports the expansion of Tregs [95][96][97].…”
Section: Np Development For Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Using similar particles, although loaded with PLP 139-151 , the authors also showed that subcutaneous injection could reduce the incidence of EAE; however, unlike intravenous infusion, protection was not 100% [5,94]. Another strategy that focuses on altering DC phenotype is the administration of NPs that agonize the ligand-activated transcription factor aryl hydrocarbon receptor [7,[95][96][97]. The activation of aryl hydrocarbon receptor on DCs supports their differentiation into tolerogenic APCs, which supports the expansion of Tregs [95][96][97].…”
Section: Np Development For Tolerancementioning
confidence: 99%
“…Another strategy that focuses on altering DC phenotype is the administration of NPs that agonize the ligand-activated transcription factor aryl hydrocarbon receptor [7,[95][96][97]. The activation of aryl hydrocarbon receptor on DCs supports their differentiation into tolerogenic APCs, which supports the expansion of Tregs [95][96][97]. Using the MOG or PLP EAE model, pegylated gold NPs loaded with the aryl hydrocarbon receptor agonist 2-(1′H-indole-3′-carbonyl)-thiazole-4-carboxylic acid methyl ester and MOG or PLP were tested for their ability to ameliorate disease [7].…”
Section: Np Development For Tolerancementioning
confidence: 99%
“…AhR activation with the nontoxic mucosal ligand 2-(1′H-indole-3′-carbonyl)-thiazole-4-carboxylic acid methyl ester (ITE) expands Tregs and suppresses EAE (11). We (11) and others (13)(14)(15) showed that the generation of Tregs by AhR ligands involves the induction of tolerogenic dendritic cells (DCs). Indeed, the activation of AhR signaling in DCs by ITE or other ligands induces DCs that promote FoxP3 + Treg differentiation (11,(13)(14)(15).…”
mentioning
confidence: 99%
“…TCDD administration also prolonged graft survival in a fully allogeneic MHC-mismatched cardiac transplant model (89). In a murine islet cell transplant model, oral administration of VAG539, a pro-agent that is converted to the AHR ligand VAF347, led to long-term graft acceptance in 69% of recipients (90). Furthermore, VAG539-induced tolerance was transferable by the adoptive transfer of CD11c + cells isolated from treated recipients.…”
Section: Impact Of Pollutants On Graft Outcomementioning
confidence: 87%